Pendampingan Bidan melalui Modul Edukasi stunting dalam Mencegah dan Mendeteksi Kejadian Stunting di Kabupaten Soppeng - Nunung Erviany; Ummul Khair; Syarifah Sahirah; Ummu Kalsum; Nur Gita Jamilda; Hasnia Hasnia; Hajar Hajar (PPNI UNIMMAN, 2024)
The stunting problem is a global nutritional problem faced by most countries in parts of the world, including in developed countries though. In developing countries, the number of children in rural areas who experience stunting is more than 50% or almost 1.5 times greater than children in urban areas. In Indonesia, the prevalence of stunting toddlers decreased from 24.4% in 2021 to 21.6% in 2022. In Indonesia, stunting is called dwarfism, meaning that there is impaired physical growth and brain growth in children. This devotional activity is carried out to train midwives in an effort to improve the midwife's ability to prevent and detect stunting events. The implementation of the Activity is carried out in a hybrid way, where participants follow 40 participants online. The methods used are lectures, discussions and simulations. The implementation of this activity is in partnership with IBI Manager Soppeng Branch. The results showed that participants filled 40 posts, of which 73.01% of the participants had good knowledge. Activities carried out in an orderly manner according to the activity plan.